Intestinal Parasites and Hematological Parameters in Children Living in Ambatoboeny District, Madagascar - Wanesa Richert; Daria Kołodziej; Danuta Zarudzka; Daniel Kasprowicz; Dariusz Świetlik; Krzysztof Korzeniewski (Pathogens)
Madagascar is one of the poorest countries in the world. The country’s extreme weather conditions, poor sanitation, and weak economy facilitate the spread of parasitic diseases. Infections with intestinal parasites are particularly dangerous for children because they can cause malnutrition and anemia, which, in turn, have a negative effect on children’s cognitive functions and physical development. The aim of the present study was to analyze the prevalence of intestinal parasites and to assess hematological parameters in a group of children living in northern Madagascar. The screening was conducted in May 2024 in the Clinique Medicale Beyzym in Manerinerina, the Ambatoboeny district. It involved a sample of 208 children aged 0–17 years. Single stool samples were collected from all study participants. The samples were fixed in SAF fixative and then transported from Africa to Europe for further diagnostics at the Department of Epidemiology and Tropical Medicine, the Military Institute of Medicine–the National Research Institute in Poland. First, the samples were analyzed by light microscopy methods using three different diagnostic techniques (direct smear, decantation with distilled water, and the Fülleborn method). Next, they were tested by molecular biology methods (real-time PCR). Blood samples for the assessment of hematological parameters were collected at the healthcare center in Madagascar. The prevalence of intestinal parasites in the study sample was 61.5%. Helminths were found in 15.2% of the investigated children, and Giardia intestinalis (20.5%) was found to be the most prevalent parasite in the study population. Most infections were caused by potentially pathogenic stramenopila Blastocystis spp. (32.0%). Mean Hb, HCT, MCV, MCH, and MCHC levels in the study participants were below normal values. However, no correlation was found between the presence of a parasitic infection and low hematological parameters, which are a clinical sign of anemia. High rates of infections with intestinal parasites in children living in northern Madagascar support the necessity to introduce long-term preventive measures, which would limit the spread of parasitic diseases in the Malagasy population. Low hematological parameters in non-infected children may be indicative of persistent malnutrition or infection with other parasites, e.g., malaria or schistosomiasis.